The potency of the adaptive cooperative learning model in strengthening numeracy performance of secondary school students: Education policy insights - Susilawati, Eni; Muslim, Suyitno; Khaerudin, Khaerudin; Yansyah, Fikri (Edelweiss Applied Science and Technology, 2024)
The students’ numeracy skills in Indonesia still need improvement. In order to strengthen numeracy skills for students, it is necessary to develop learning strategies that provide a fun and engaging learning environment for students by life involving the roles of parents, peers, and the community. This study aims to evaluate the effectiveness of the Adaptive Cooperative Learning model, developed by the researchers. Using a quasi-experimental design, the research involved a Cohort of around 32 students who participated in the product testing phase. The study incorporated a pretest, an experimental period, and a post-test. The findings revealed a marked improvement in student performance following the implementation of the Adaptive Cooperative Learning model, with the average score increasing to 79.44 and a standard deviation of 9.9. This equates to an N-gain of 0.77, which falls within the high range, suggesting that the model is effective in enhancing numeracy performance. The study concludes with several policy insights aimed at shaping future educational reforms in Indonesia, specifically in the area of numeracy teaching.